Earthworm (Oligochaeta, Lumbricidae) intraspecific genetic variation and polyploidy - S. V. Shekhovtsov; Ye. A. Derzhinsky; E. V. Golovanova (Вавиловский журнал генетики и селекции, 2024)
Earthworms are known for their intricate systematics and a diverse range of reproduction modes, including outcrossing, self-fertilization, parthenogenesis, and some other modes, which can occasionally coexist in a single species. Moreover, they exhibit considerable intraspecific karyotype diversity, with ploidy levels varying from di- to decaploid, as well as high genetic variation. In some cases, a single species may exhibit significant morphological variation, contain several races of diﬀerent ploidy, and harbor multiple genetic lineages that display significant divergence in both nuclear and mitochondrial DNA. However, the relationship between ploidy races and genetic lineages in earthworms remains largely unexplored. To address this question, we conducted a comprehensive review of available data on earthworm genetic diversity and karyotypes. Our analysis revealed that in many cases, a single genetic lineage appears to encompass populations with diﬀerent ploidy levels, indicating recent polyploidization. On the other hand, some other cases like Octolasion tyrtaeum and Dendrobaena schmidti/D. tellermanica demonstrate pronounced genetic boundaries between ploidy races, implying that they diverged long ago. Certain cases like the Eisenia nordenskioldi complex represent a complex picture with ancient divergence between lineages and both ancient and recent polyploidization. The comparison of phylogenetic and cytological data suggests that some ploidy races have arisen independently multiple times, which supports the early findings by T.S. Vsevolodova-Perel and T.V. Malinina. The key to such a complex picture is probably the plasticity of reproductive modes in earthworms, which encompass diverse modes of sexual and asexual reproduction; also, it has been demonstrated that even high-ploidy forms can retain amphimixis.